GAMBARAN PSIKOLOGI WARGA KABUPATEN MAGELANG SELAMA PANDEMI COVID-19 - Muhammad Khoirul Amin; Sambodo Sriadi Pinilih; Retna Tri Astuti (Jurnal Ilmiah Keperawatan, 2021)
Magelang Regency was ranked first in the case of Covid-19 in Central Java in May 2020. Covid-19 has both physical and psychological impacts. Stress, anxiety and depression are the biggest impacts of the COVID-19 pandemic. This study aims to find out how the psychological view of the residents of Magelang Regency during the covid-19 pandemic. The design of this research is descriptive research, with the aim of knowing the psychological view of the Magelang district community during the covid pandemic. This study was conducted on 62 respondents aged > 15 years in Magelang Regency using the SRQ-29 questionnaire (self-reporting questionnaire-29). From the SRQ-29 which was distributed to the respondents, it was found that there were respondents who had problems with mental emotional disorders, psychotic disorders and PTSD and there were no respondents who used psychotropic substances. During this COVID-19 pandemic, there were respondents who experienced mental emotional disorders, psychotic disorders and also PTSD.